Penerapan Algoritma Naïve Bayes dalam mengklasifikasikan Media Sosial untuk mengamati Trend Kuliner - Wilandini, Destaria; Purwantoro, Purwantoro (Jurnal Teknologi Terpadu, 2022)
The influence of the internet and social media has accelerated the pace of business trends developing rapidly, and social media acts as a means of information and information warehouses in observing emerging trends. In this study, the Naïve Bayes algorithm was used to analyze and predict social media applications by classifying classes on the data to see which applications are most popular with the public in observing a culinary trend. Culinary business trends choose as the subject under study with the object of research on social media applications. Social media is researched to produce recommendations for social media applications that are suitable for use in marketing media based on their target market, the dataset used was 101 data with 80%:20% split data. The study results stated that using the Tiktok application is recommended, after Instagram, Twitter, Youtube, and finally, Facebook. This research was conducted for MSMEs to guide suitable social media applications in business marketing strategies. Based on the results of this study, research experiments using other methods and algorithms can be applied in other studies to be a comparison with the current research results.